Methods of health-improving classes according to the hatha yoga system with women 36-40 years old - M.V. Bazilevich; E.A. Simonova; M.V. Kolykhalova (Theory and Practice of Physical Culture, 2023)
Objective of the study was the theoretical and methodological substantiation of the methodology of health-improving classes according to the Hatha Yoga system with women aged 36-40. Methods and structure of the study. The goal of health-improving training was to ensure the correction of age-related disorders and the prevention of pathological changes in the body. When organizing health-improving classes, considerable attention was paid to the motives, needs, and interests of those involved. A pedagogical study lasting nine months was organized with the participation of 22 women (EG-11 people, CG-11 people) aged 36-40 years on the basis of the «Millennium» fitness center. All participants in the pedagogical experiment belonged to the main medical group. Results and conclusions. The peculiarity of the developed methodology of health-improving classes with women aged 36-40 was the use of Vyayama articular gymnastics, Surya Namaskar asanas, breathing techniques, which made it possible to achieve significant results in physical fitness, functional and psycho-emotional state of women from the EG.